Translation Inhibition by Rocaglates Activates a Species-Specific Cell Death Program in the Emerging Fungal Pathogen Candida auris - Kali R. Iyer; Luke Whitesell; John A. Porco; Thomas Henkel; Lauren E. Brown; Nicole Robbins; Leah E. Cowen (mBio, 2020)
ABSTRACT Fungal infections are a major contributor to infectious disease-related deaths worldwide. Recently, global emergence of the fungal pathogen Candida auris has caused considerable concern because most C. auris isolates are resistant to fluconazole, the most commonly administered antifungal, and some isolates are resistant to drugs from all three major antifungal classes. To identify novel agents with bioactivity against C. auris, we screened 2,454 compounds from a diversity-oriented synthesis collection. Of the five hits identified, most shared a common rocaglate core structure and displayed fungicidal activity against C. auris. These rocaglate hits inhibited translation in C. auris but not in its pathogenic relative Candida albicans. Species specificity was contingent on variation at a single amino acid residue in Tif1, a fungal member of the eukaryotic initiation factor 4A (eIF4A) family of translation initiation factors known to be targeted by rocaglates. Rocaglate-mediated inhibition of translation in C. auris activated a cell death program characterized by loss of mitochondrial membrane potential, increased caspase-like activity, and disrupted vacuolar homeostasis. In a rocaglate-sensitized C. albicans mutant engineered to express translation initiation factor 1 (Tif1) with the variant amino acid that we had identified in C. auris, translation was inhibited but no programmed cell death phenotypes were observed. This surprising finding suggests divergence between these related fungal pathogens in their pathways of cellular responses to translation inhibition. From a therapeutic perspective, the chemical biology that we have uncovered reveals species-specific vulnerability in C. auris and identifies a promising target for development of new, mechanistically distinct antifungals in the battle against this emerging pathogen. IMPORTANCE Emergence of the fungal pathogen Candida auris has ignited intrigue and alarm within the medical community and the public at large. This pathogen is unusually resistant to antifungals, threatening to overwhelm current management options. By screening a library of structurally diverse molecules, we found that C. auris is surprisingly sensitive to translation inhibition by a class of compounds known as rocaglates (also known as flavaglines). Despite the high level of conservation across fungi in their protein synthesis machinery, these compounds inhibited translation initiation and activated a cell death program in C. auris but not in its relative Candida albicans. Our findings highlight a surprising divergence across the cell death programs operating in Candida species and underscore the need to understand the specific biology of a pathogen in attempting to develop more-effective treatments against it.